Sotrack / Muhammad Nur Adhzani Muhammad Shukri ...[et al.] - Muhammad Shukri, Muhammad Nur Adhzani; Ahmad Hanit, Muhammad Hakim; Za'adun, Siti Nur Hidayah; Jaferi, Nur Izatul (2019)
SoTrack is our product that innovated from current fixed ground-mount solar panels. Our company decide to make changes and improve towards this current product to increase its efficient on power generation, harness power from the sun ray to the max and reduces the amount of real estate needed for the system. The problem with the current fixed ground - mount solar panels is they do not rotate and do not aim directly to the sun as the sun moves over time. This means the orientation of the solar panels is kept unchanged during the entire year. As a result, the lesser the sunlight been harvested. But with small adjustment would be advantageous. Solar power, with its promise of emissions-free renewable energy, boasts a growing number of fans. Some of them, it turns out, are thieves, and a lot of cases of solar panels being stolen have been reported. And lastly, it requires large amounts of solar panel and requires large amounts of land either. It would take around three to four sheets of the solar panel to be able to produce the same amount of electricity as that of a single solar tracker. The unique part about our product is it has two rotation axis degrees, which are called the "primary axis" and the "secondary axis." The rotational axis can move downwards or upwards to adjust with the angles of the sun throughout the day. SoTrack allows for the most accurate orientation of the solar device, and it provides 40% more output through energy absorption and can maximize energy production.